Traditional Uses, Chemistry, Pharmacology, Toxicology and Quality Control of Alhagi sparsifolia Shap.: A Review - Wei, Feng; Yang, Xinzhou; Pang, Kejian; Tang, Hui (Frontiers in Pharmacology, 2021)
Alhagi sparsifolia Shap. (Kokyantak) a member of the family Leguminosae, is distributed in China, Kazakhstan, Uzbekistan, Turkmenistan, Kyrgyzstan and Tajikistan. Traditionally, it has been used in the Uyghur system of medicine for the treatment of colds, rheumatic pains, diarrhea, stomach pains, headaches and toothaches, in addition to being an important local nectar plant and high-quality forage grass, and playing an important role in improving the ecological environment. Currently, approximately 178 chemical constituents have been identified from A. sparsifolia, including flavonoids, alkaloids and phenolic acids, and 19 polysaccharides. Among them, flavonoids and polysaccharides are predominant and characteristic constituents. The purified extracts and isolates show exhibits extensive pharmacological activities, such as antioxidant, anti-tumor, anti-neuroinflammatory, protective effects on liver and renal injury. Some of the available toxicological tests and quality control studies have proved that A. sparsifolia is safe and non-toxic. This review presents for the first time the A. sparsifolia in the Uyghur system of medicine and provides a comprehensive summary of the traditional use and chemical composition. Botany, pharmacology, quality control and toxicology are also listed. Based on a comprehensive investigations of A. sparsifolia, we believe that A. sparsifolia is a valuable and abundant medicinal resource with promising therapeutic properties and important potential for exploitation. Going forward, more comprehensive studies on origin identification, characterization of active ingredients, pharmacological mechanisms, quality control and toxicology are extremely important to demonstrate the clinical efficacy and safety of A. sparsifolia extracts and their isolated bioactive components.